Homework: considerations about its impact in the overall scholar life (Journal of Parents and Teachers, 2014)
Following the research-action methodology, the homework question is analized from the family perspective, taking into account the impact that it has in both social and educative levels in social, familiar, scholar and personal environments of the pupil.
Keywords: Homework; reflection; review proceedings; education; a look at education